Morbidity patterns of persons in prisons compared to the general Hungarian population between 2017 and 2019 - P. Fadgyas-Freyler; Á. Münnich; J. Molnár; K. Kósa (Public Health in Practice)
Objectives: Prison population around the globe tends be among the most marginalized population groups. Many of these persons struggle with numerous health problems, primarily with infectious diseases and mental disorders. Our goal was to analyse morbidity of prisoners compared to age- and gender-matched controls. Study design: Case-control study based on administrative data of healthcare utilisation in Hungary between 2017 and 2019. Methods: Patient numbers by ICD-10 chapters and tabulation lists of diagnosis (morbidity groups) were obtained from the government-funded single payer health insurance institute. Convicts were compared to controls matched by age and gender in a 5:1 ratio. Results: The leading causes of healthcare utilisation of prisoners compared to controls by ICD-10 chapters were mental and behavioural disorders and external causes of morbidity, but the relative risk of healthcare use due to infectious diseases was not elevated. When investigating data at a more detailed level, that is, by morbidity groups, the relative risk of healthcare utilisation due to 19 out of a total of 299 morbidity groups was significantly, more than 3 times higher among prisoners compared to controls, and the first five highest relative risks were all due to external causes of injury. Conclusion: The leading causes of morbidity among persons in prisons based on health care utilisation seems to be somewhat different from morbidity patterns identified by other methods such as clinical interviews, screening or estimations. Causes of health care utilisation both at ICD chapter and morbidity group-level is one of several relevant indicators of the health care needs of prison populations that uncovers the groups of most severe maladies among them. However, other sources of data should also be taken into account for the development of effective preventive and rehabilitative interventions. Follow-up of prisoner patients treated in health care would also be recommended to aid rehabilitation.